Nanoengineering : global approaches to health and safety issues - Dolez, Patricia I. (Amsterdam : Elsevier, 2015)
Nanoengineering: Global Approaches to Health and Safety Issues provides a global vision on the impact of engineered nanomaterials both for the consumer/general public and in occupational settings. The book also presents a hint on what can be expected for the future from nanomaterials and their effects on our lives, both at home and at work. In addition, users will find valuable information on nanomaterials' irreplaceable value and their risks for health, safety, and environmental issues. Case studies illustrate key points and provide information on important processes.
Includes bibliographical references and index.
Online resource; title from PDF title page (Ebsco, viewed June 3, 2015).
Elsevier
Keywords: Nanoparticles -- Health aspects; Nanoparticles -- Safety measures; Nanotechnology -- Health aspects; Nanotechnology -- Safety measures; SCIENCE / Nanoscience; TECHNOLOGY & ENGINEERING / Nanotechnology & MEMS; Electronic books; Electronic books